Estudo ultrassonográfico pré-natal na gastrosquise: que sinais influenciam no desfecho perinatal? - Dias, Cristiane de Moraes (2017)
Gastroschisis is a congenital malformation characterized by a closure defect of the anterior abdominal wall; paraumbilical. It is almost always at the right side, where abdominal organs are externalized. In recent decades, the frequency of this condition has become more common. Some risk factors are: young maternal age, primiparity, smoking, use of illicit drugs and exposure to some vasoconstricting drugs. The benefits of the prenatal diagnosis of gastroschisis are well established: family preparation and support, and birth adequate planning by a multidisciplinary team. The identification of ultrasound markers of complex cases during prenatal care has advantages for parental counseling and concentrating efforts to improve support for the newborns. Objectives: To correlate the findings of prenatal ultrasonography of gastroschisis with the perinatal morbimortality; to evaluate whether any sign in the ultrasound screening could point out the severity of disease . To characterize pregnant women diagnosed with gastroschisis attended at the Interdepartmental Center of Fetal Medicine (CIMEFE) as well as their newborns submitted to surgical interventions in the neonatal period. Patients and Methods: This retrospective cohort study comprised 33 cases of gastroschisis diagnosed at the CIMEFE from April 2005 to October 2016. The antenatal ultrasound examinations were evaluated in addition to the medical records of the pregnant women and their newborns. The presence of at least one of the following factors was defined as an unfavorable outcome: perinatal death, sepsis and need for surgical reintervention or intestinal resection. Results: The mean maternal age was 20.5 years, and 72.7% were primigravidae. The delivery was at the 35.6 week-average gestational age. The findings described in prenatal ultrasonography were extra-abdominal intestinal loop dilatation (48.5%), presence of associated fetal malformations (21.2%), exteriorization of the bladder (15.2%), intra-abdominal intestinal loop dilatation (12.1%), exteriorization of the stomach (12.1%), polyhydramnium (12.1%), oligohydramnium (9.1%), distension of the stomach (6.1%) and exteriorization of the liver (3.0%). At birth, 9.1% of the newborns presented intestinal changes (atresia and/or ischemia). Intrauterine and postnatal deaths occurred in 3.0% and 15.1%, respectively. Unfavorable outcomes were observed in 54.5% of the cases. During neonatal evolution, 50% of newborns had sepsis, 12.5% needed surgical reinterventions and 12.5% suffered intestinal resection. The risk of an unfavorable outcome was twice as high in newborns with exteriorization or distension of the stomach or exteriorization of the liver. The exteriorization of the liver increased the risk of death by six times. However, due to the small number of affected cases, no statistical significance was found. Conclusion: Prenatal ultrasonographic findings such as distension of the stomach, exteriorization of the stomach or exteriorization of the liver may guide the prediction of perinatal outcomes, but further multicenter studies are needed to improve prenatal care and counseling to this specific population. Data of this study sample were according to the literature regarding the characterization of pregnant women and their newborns.